Efek Cycling Terhadap Fungsi Kognitif Pada Lanjut Usia : Effects of Cycling on Cognitive Function in the Elderly - Rahmi, Upik; Lisna Anisa Fitriana; Suci Tuty Putri; Septian Andriyani (JSH: Journal of Sport and Health, 2024)
ABSTRACT It has been shown that both exercise and environmental stimulation can improve cognitive function and well-being in older adults. However, the combined effects of outdoor exercise on psychological function have not been widely studied. This study aimed to explore the impact of an outdoor cycling intervention on cognition and mental health. A total of 52 participants aged 50-83 years were involved in the study, with 26 as a non-cycling control group, 26 cycling using a conventional pedal bicycle. Participants who cycled were required to cycle at least three times a week for 30 minutes over an eight-week period. Cognitive function and well-being were measured before and after the intervention. Results showed increased accuracy in executive function, updating (Letter Updating Task), in both cycling groups compared to the control group. In addition, participants experienced improved mental health after the intervention, compared to the control group. These results suggest a positive impact of cycling in the outdoor environment on executive function and mental health.